Liquid Culture Systems for in vitro Plant Propagation - Hvoslef-Eide, A.K. (Springer, 2012)
This book describes very well recent developments in liquid culture system for in vitro plant propagation. It will be an excellent source of information to the researchers for refining methodologies on large-scale plant propagation and secondary metabolite production. … This book is highly recommended to the researchers and students, and libraries." (S. Mohan Jain, Plant Cell, Tissue and Organ Culture, Vol. 84, 2006)